If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -114 + -10x = 54 + 4x Solving -114 + -10x = 54 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -114 + -10x + -4x = 54 + 4x + -4x Combine like terms: -10x + -4x = -14x -114 + -14x = 54 + 4x + -4x Combine like terms: 4x + -4x = 0 -114 + -14x = 54 + 0 -114 + -14x = 54 Add '114' to each side of the equation. -114 + 114 + -14x = 54 + 114 Combine like terms: -114 + 114 = 0 0 + -14x = 54 + 114 -14x = 54 + 114 Combine like terms: 54 + 114 = 168 -14x = 168 Divide each side by '-14'. x = -12 Simplifying x = -12
| 3x+2x+6=31 | | -3(x+6)=5-(-3) | | 26=4x-6 | | 8x+9=2x-15 | | onethird(6x-9)=5x+2(x+9) | | 6v*4h+2v-h=77 | | 5m+3(4)=22 | | 3a-2=19 | | -16+9x=5x+-30 | | M-3x=2x | | -5x-16=-7x+26 | | -8r=-8r-5r | | -5(x+5)=4-(-3) | | -8r=-8r-5 | | 7w-8w=-4-30 | | 10(2x-1)+5(4x+3)=-115 | | 24=5-(3-2m) | | 3x^2+63=30x | | 12y-7y+2y= | | 5-k=11-k | | 3(3)-4y=7 | | -(4y+2)-(-3y-4)=-4 | | 12x+60=13x+2 | | 8y(8+6y)=20 | | 12x-8=3x-35 | | 5x=3(x+3) | | 54x+14=43x+14 | | 7-3(2x-5)=5(3x+4)+2x | | 3x^2-6+2=26 | | 8x^2-6x=-9 | | 4x-24=3x+3 | | x-4.3=1.8 |